(untitled) (Advances in Civil and Architectural Engineering, 2025)
High-rise building projects face a significant problem with safety mishaps due to insufficient safety performance. This study aims to examine the factors that contribute to safety performance in high-rise building projects by utilising a combined approach of exploratory factor analysis (EFA) and structural equation modelling (SEM). A total of 400 questionnaires were disseminated and as a result, 285 valid replies were obtained, indicating a response rate of 71 %. In order to accomplish the objective of this research study, EFA was used to identify eight safety-related factors that impact the safety performance of high-rise building projects. The results indicated that the factor F8 (mishandling construction material) was eliminated from the final structural equation model because it did not have an adequate statistically significant value. The final structural equation model passed the goodness-of-fit tests and hypothesis testing, indicating the model’s validity. Consequently, using EFA and SEM methodologies offers a framework for future researchers to accomplish specific goals in the construction sector and enhance safety management in high-rise building projects. The study’s findings will serve as a foundation for numerous industry players to mitigate hazardous situations and enhance the efficiency of high-rise building projects via the application of safety management concepts.